Transforming growth factor-β1 and eosinophil-derived neurotoxins contribute to the development of work-related respiratory symptoms in bakery workers - Hoang Kim Tu Trinh (World Allergy Organization Journal, 2019)
Background: In baker's asthma previous studies suggest that adaptive and innate immunity are involved in the development of work-related respiratory symptoms (WRS), where we hypothesized that epithelial cells derive airway inflammation through modulating the release of inflammatory cytokines. Thus, we conducted this study to investigate the role of epithelial cell-derived cytokines in the development of WRS among bakery workers. Methods: We recruited 385 wheat-exposed subjects with WRS (WRS+)/without WRS (WRS-) working in a single industry and 243 unexposed controls from Ajou Medical Center (Suwon, South Korea). Levels of epithelial cell-derived cytokines (interleukin [IL-8], transforming growth factor-β1 [TGF-β1], eotaxin-2) and inflammatory mediators (eosinophil-derived neurotoxins [EDN]) in sera or cell-free supernatants were measured by ELISA. Human airway epithelial cells (HAECs), A549, were stimulated by wheat flour extracts and co-cultured with peripheral blood neutrophils isolated from 4 asthmatic patients. Results: Serum TGF-β1 levels were significantly lower in exposed subjects than in unexposed controls, in the WRS+ group than in the WRS- group (P < 0.001 for each). The WRS+ group had a significantly higher level of serum EDN than the WRS- group (P < 0.001). Serum TGF-β1 and EDN levels predicted the development of WRS in exposed subjects (area under the curve [AUC] = 0.719, 72.4% sensitivity/70% specificity; AUC = 0.759, 78.6% sensitivity/60% specificity). From wheat-stimulated HAECs, TGF-β1 release peaked at 6 hours after wheat exposure, while eotaxin-2 peaked at 12 hours. Co-culture of HAECs with neutrophils did not affect TGF-β1 release. Conclusions: Our results suggest that TGF-β1 may contribute to develop type-2 airway inflammation and WRS. Serum TGF-β1/EDN levels may be potential serum biomarkers for predicting WRS among bakery workers. Keywords: Bakery workers, Work-related symptoms, Transforming growth factor β1, Eosinophil-derived neurotoxin